2011
DOI: 10.1007/s12070-011-0382-8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Metabolic Presbycusis and Serum Paraoxonase/Arylesterase Activity

Abstract: To determine the presence of a relationship between metabolic presbycusis and serum paraoxonase/ arylesterase activity. A total of 30 patients who had been admitted to the Ear, Nose, and Throat (ENT) Clinic of Fırat University Medical Faculty and diagnosed as metabolic presbycusis were included in the study. The control group was composed of 30 healthy volunteers. Pure tone audiometry and impedencemeter were performed on all subjects included in the study at the audiometry laboratory of the ENT clinic. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Presbycusis has a major impact on the quality of human life, and is related to a reduce communication skills, social isolation and possibly exacerbating anxiety-depressive status [7]. The degenerative processes of presbycusis are probably influenced by many factors such as heredity, environmental and systemic comorbidities such as hyperlipidemia, many studies tried to evaluate this relationship, but it is still subject to question [8].…”
Section: Discussionmentioning
confidence: 99%
“…Presbycusis has a major impact on the quality of human life, and is related to a reduce communication skills, social isolation and possibly exacerbating anxiety-depressive status [7]. The degenerative processes of presbycusis are probably influenced by many factors such as heredity, environmental and systemic comorbidities such as hyperlipidemia, many studies tried to evaluate this relationship, but it is still subject to question [8].…”
Section: Discussionmentioning
confidence: 99%
“…Keles et al [7] compared serum level of metabolic presbycusis patients and control group and reported that total cholesterol was found to be statistically significantly high in those with presbycusis. Our findings disagree with Jones and Davis [24] who found that the study of 85 patients with sensorineural hearing loss showed no significant difference between their cholesterol level and that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Atrofi ini menyebabkan gangguan pendengaran. 14 Pada penelitian ini didapatkan penderita presbikusis yang disertai riwayat kronik seperti hipertensi dan DM tipe II. Hipertensi dan DM tipe II dapat memacu proses gangguan pendengaran pada lansia.…”
Section: Diskusiunclassified